Dampak Anxiety pada Mahasiswa Komunikasi dan Penyiaran Islam dalam Proses Pembelajaran di Fakultas Dakwah dan Komunikasi - Ainul Mardiyah; Juleha Juleha; Zahratun Muna; Faiz Martua Azhari Hasibuan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
University students often face psychological challenges, one of which is anxiety, which can negatively affect learning and academic performance. This study aims to explore the anxiety experienced by students of the Islamic Communication and Broadcasting (KPI) Department at the Faculty of Da'wah and Communication, particularly during classroom presentations. A qualitative method was employed, using in-depth interviews with selected KPI students as participants. The findings reveal that anxiety is triggered by academic pressure, social expectations, and a lack of self-confidence. The impacts include reduced concentration, difficulty speaking in public, and challenges in expressing ideas. Despite these issues, students employ various coping strategies, such as thorough preparation, individual practice, and support from peers. These findings are expected to contribute to the development of a more supportive learning environment that considers students' mental well-being.